Software Defect Prediction : Literature Study - Hermawan Hermawan; Santun Irawan (Annual Research Seminar (ARS), 2015)
Abstract - Software Defect Prediction is a scientific methods which is used to predict errors, bugs , failures in software.  This technique will be very helpful in System Development Life Cycle (SDLC) process, especially for software testing part. This method can also be used to ensure the quality of software development, through software metrics even before the software is not yet built. In the end all of this will save time and cost in the project. This study has been generally will produce a dataset , methods , and frameworks , both held in the set of samples or on the actual software project. Keywords : Software defects , errors , defects Study software